Implementasi Metode Sad Dharma Penyuluhan Agama Hindu Pada Masa Pandemi Covid-19 - I Nyoman Buda Asmara Putra; Gede Agus Jaya Negara (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2020)
The COVID-19 pandemic that occurred in Indonesia changed all lines of human life, both in the fields of education, health, economy, politics, socio-culture and religion. In the religious field, the challenges of Hindu extension workers in carrying out guidance for people during this pandemic are getting heavier. Prior to the pandemic, out reach was carried out by communicating directly with the community both in temples, bale banjar, prisons, orphanages and other places with an unlimited number of participants. Now all human activities are limited, including Hindu religious counseling, it is obligatory to apply and participate in disseminating health protocols to the community. The health protocols that must be implemented are physical distancing, avoiding crowds, using masks and getting used to washing hands with soap to prevent transmission of the corona virus. The implementation of the sad dharma method of Hindu religious extension workers must also adjust to this pandemic. There are two coaching strategies during this pandemic, first online, using social media and offline, namely interacting, communicating face to face with the community. The two strategies can be implemented in the respective target areas in accordance with the situation and conditions.Keywords: Implementation, Sad Dharma Method, Hindu Religious Counseling, COVID-19 Pandemic